Psychological problems in adolescents of the Republic of Tuva with different types of online behavior - Zaitseva, Olga I.; Tereshchenko, Sergey Yu.; Kolodyazhnaya, Tatyana A.; Zaytseva, Zhanna G. (The New Research of Tuva, 2024)
The article analyzes the psychological problems of adolescents with different online behaviors in the Republic of Tuva. It is based on the results of two psychological surveys conducted by the author in April and May of 2022 and 2023, respectively, in the republic. A total of 265 participants (173 Tuvan and 92 Russian) were surveyed. The screening questionnaire “Strengths and Difficulties” by R. Goodman was used for this study.For all surveyed adolescents, an increase in psychological problems was found to be an undesirable sign of Internet addiction. Dominant psychological issues have been identified among adolescents with similar online behaviors, depending on ethnic, gender, and age differences.The most prevalent psychological problems among Tuvan adolescents were communication issues with peers (23.1–42.4%). Additionally, psychological issues related to the age group were also communication problems with peers, occurring 2 to 2.5 times more frequently (36.6–43.2%) among adolescents aged 12–14 with adaptive and maladaptive internet use.When differentiating by gender, girls with maladaptive internet use do not exhibit the best indicators compared to boys in the same group. Emotional disorders are 2.2 times more common (39.1%), and communication issues with peers are 2.1 times more prevalent (43.4%). Russian teenagers with maladaptive internet use experience problems communicating with their peers, general psychological issues, and difficulties adapting. These issues affect 27.9%, 25.5%, and 20.9% of teenagers, respectively.
Keywords: Republic of Tuva; teenager; Tuvans; Russians; online behavior; internet addiction